2005
DOI: 10.1074/jbc.m504792200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of FTDP-17 Mutant tau by Cyclin-dependent Kinase 5 Complexed with p35, p25, or p39

Abstract: Neurofibrillary tangles are one of the major pathological hallmarks of Alzheimer disease (AD).1 Neurofibrillary tangles are bundles of paired helical filament composed of the microtubule (MT)-associated protein tau in a hyperphosphorylated state (1, 2). Intracellular inclusions made of tau are also found in several other neurodegenerative diseases, including Pick disease, progressive supranuclear palsy, corticobasal degeneration, and frontotemporal dementia and Parkinsonism linked to chromosome 17 (FTDP-17), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 47 publications
7
62
0
Order By: Relevance
“…p35 is cleaved to p25 by calpain to generate Cdk5/p25, which has increased kinase activity (Patrick et al, 1999;Hisanaga and Saito, 2003;Sakaue et al, 2005). We observed a similar inhibitory effect of Cdk5/p25 on inclusions (Fig.…”
Section: Suppression Of Mhtt Aggregate Formation By Cdk5/p35supporting
confidence: 71%
See 3 more Smart Citations
“…p35 is cleaved to p25 by calpain to generate Cdk5/p25, which has increased kinase activity (Patrick et al, 1999;Hisanaga and Saito, 2003;Sakaue et al, 2005). We observed a similar inhibitory effect of Cdk5/p25 on inclusions (Fig.…”
Section: Suppression Of Mhtt Aggregate Formation By Cdk5/p35supporting
confidence: 71%
“…The binding of Cdk5 or p35 with tNhtt-poly(Q)-EGFP was examined by immunoblotting with anti-Cdk5 or anti-p35 antibody after immunoprecipitation of tNhtt-poly(Q)-EGFP from COS-7 cells with anti-GFP antibody . The longer 90Q form was phosphorylated by Cdk5/p25 purified from Sf9 cells in MOPS (3-morpholinepropanesulfonic acid) buffer containing 0.5% Nonidet P-40 and [␥-32 P]ATP (0.1 mM) for 30 min at 35°C (Sakaue et al, 2005). Phosphorylation was estimated by a FLA7000 Image Analyzer (Fuji Film) after SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with early work by Kusakawa et al,. who measured the activity of immunoprecipitates of these enzymes (46), and Sakaue et al, who tested both enzymes against several FTDP-17 mutants of tau (47). Recently, Maestras et al (48) reported that CDK5/p25 is significantly more active than CDK5/p35 toward the anaphase-promoting complex factor, cdh1, suggesting that differential enzyme activity may be substrate-dependent.…”
Section: Discussionmentioning
confidence: 99%